Problematika Guru Matematika Pada Pembelajaran Matematika di SMP Muhammadiyah 3 Depok - Muna, Khozainul; Hidayati, Fina Hanifa (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2023)
One of the causes of difficulties in studying mathematics is the interaction between teachers and students. Teaching and learning are the two types of activities that go into the process of learning mathematics. Combining these two exercises creates a task that encourages communication between students, teachers, and other students. The teacher is a mentor and an example for the students, acting as an educator. This research intends to outline the difficulties math teachers have when teaching students at SMP Muhammadiyah 3 Depok. The technique is a qualitative strategy. An teacher of mathematics at SMP Muhammadiyah 3 Depok served as the research subject. Techniques for collecting data through interviews. According to research, there are three issues that math teachers at SMP 3 Muhammadiyah 3 Depok must deal with:1) poor time management, 2) a discrepancy between the methods used and what was planned, 3) a discrepancy between the material being taught and the ASPD exam material.